Three essays on international trade policies - YI, Xin (Institutional Knowledge at Singapore Management University, 2020)
This dissertation studies the empirical and quantitative implications of trade policies. The first chapter examines the effects of trade policies on quality specialization across cities within a country. Specifically, we complement the quality specialization literature in international trade and study how larger cities within a country produce goods with higher quality. We first establish three stylized facts on how product quality is related to agglomeration, firm productivity, and worker skills. We then rationalize these facts in a spatial equilibrium model where all the elements mentioned above are present and firms are free to choose their locations. Using firm-level data from China, we structurally estimate the model and find that agglomeration and spatial sorting of firms each accounts for about 50% of the spatial variation in quality specialization. A counterfactual to relax land use regulation in housing production raises product quality in big cities by 5.5% and indirect welfare of individuals by 6.2%. The second chapter zooms into distributional issues and studies the implication of rising income inequality on product price dispersion. Using big data on a broad set of goods sold in the US (Nielsen Retail Scanner Data) from 2006 to 2017, we find that in general there is a missing middle phenomenon, where the product price distribution loses its mass in the middle price support. In addition, we find that this pattern is more pronounced in the densely populated metropolitan areas. We further link this observation to changes in income inequality, which are measured from a panel of US households from 2006 to 2017 (IPUMS ACS). The results support our conjecture that demand-side demographics has a significant influence on the missing middle phenomenon. The third chapter examines the transition dynamics of trade liberalization. In particular, we develop a multi-country, multi-sector quantitative trade model with dynamic Roy elements such as occupational choice and occupation-specific human capital accumulation. Given an abrupt trade liberalization, a country that is relatively more productive in some sectors may not have comparative advantage initially, as it takes time to accumulate occupation-specific human capital which increases occupational skill supply endogenously. We quantify this transition dynamics and its distributional consequences by calibrating the model to a North-South setup.